Analysis of Factors Affecting Capital Buffer in Sharia Commercial Banks in Indonesia - S. Muljaningsih; Muchtolifah; Asmara, Kiky (Future Science, 2020)
Capital buffer serves to anticipate the risk of unexpected banking systemic risks. Capital buffer is derived from the difference between banks’ capital adequacy ratio (CAR)and the minimum capital adequacy ratio (minimum CAR) regulated by policymakers. This research is made to know what factors affect capital buffer in Indonesia Islamic Commercial banks. These factors include Return On Equity (ROE), Non-Performing Finance (NPF), Financing to Deposit Ratio (FDR), and Gross Domestic Product (GDPG). This study uses secondary data obtained from the official website of OJK, the official website of the Islamic banks, and BPS Agency for a period of 5 years in 2014-2018 on quarterly data. The analysis technique used is Multiple Linear Regression Analysis. The results show that the Return on Equity (ROE), Non-Performing Finance (NPF), Financing to Deposit Ratio (FDR), and Gross Domestic Product (GDPG) affected Capital Buffer in Islamic Commercial Banks in Indonesia simultaneously. While it is partially obtained that the Financing to Deposit Ratio (FDR) variable has a significant and negative effect on the Capital Buffer. Return On Equity (ROE) and Non-Performing Finance (NPF) has insignificant and negative effects on the capital buffer. Gross Domestic Product Growth has an insignificant and positive effect on the capital buffer at Islamic Commercial Banks in Indonesia.